Study on the products of technology “Tenuun” tea (Mongolian Journal of Botany, 2023)
We had chosen the Glycyrhizia uralensis Fisch, Thymus gobicus Tczern, Thermopsis lanceolate R.Br, and Chamaenerion angustifolium L. as a biological supplement based on traditional and modern medical knowledge. In order to develop the (Tenun tea) technology, tea has been divided into seven different variations based on its clinical characteristics, and biologically active compounds were determined along with the standard of drug pharmacopeia method.As a result, variation IV was chosen, because of the most appropriate and it was determined that it corresponded with the MNS 5131:2002, MNS 5743:2007, and MNS ISO 4286:2000 standards of national tea standard. In a laboratory under expert supervision, tea samples were microbiologically analyzed in 2022 to determine whether they conformed to cleanliness standards. The procedure of tea technology was established, the tea production scheme was purified and packaged, the tea box and packaging design were made, the product model was produced, the bar code was confirmed, and after all these procedures, the tea already entered the trademark, also intellectual property patent was submitted.This tea has plenty of advantages, which are made of medicinal plants used in traditional medicine, is a research-based herbal product with benefits for the lungs, expectoration, clearing of airway or throat irritation, antibacterial and virus activity, as well as a protective effect against colds and the flu.“Тэнүүн” цай гарган авах технологийн судалгааХураангуй: Бид уламжлалт мэдлэгт тулгуурлан цэр ховхолж, хий ханиалга намдаах, амьсгалын замыг цэвэрлэх үйлдэлтэй мөн бактер, вирусын эсрэг идэвхтэй байгалийн ургамлууд болох Урал чихэр өвс (Glycyrhizia uralensis Fisch) Говийн ганга ( Thymus gobicus Tczern), Юлдэн тарваганшийр (Thermopsis lanceolate R.Br), Нарийннавчит хөвөноройт (Chamaenerion angustifolium L.) ургамлуудыг сонгон авч, ханиад томууны үед эмчилгээнд хэрэглэх, урьдчилан сэргийлэх үйлдэл бүхий биологийн нэмэлт бүтээгдэхүүн болох “Тэнүүн цай”-г гарган авлаа. Үүний тулд эдгээр 4 зүйл эмийн ургамлын ашиглагдах хэсгийг хатаан нунтаглаж, 7 хувилбараар хольж найруулан, биологийн идэвхт нэгдлийг эмийн фармокопейн стандарт арга зүйн дагуу хийж гүйцэтгэсэн. Ингэхэд IV хувилбар нь хамгийн тохиромжтой бөгөөд цайны MNS 5131:2002, MNS 5743:2007, MNS ISO 4286:2000 стандартад нийцэж байгааг тогтоолоо. Цайны дээжийг 2022 онд мэргэжлийн хяналтын ХАБҮЛабораторид микробиологийн шинжилгээнд хамруулж, эрүүл ахуйн шаардлага хангаж буйг тодорхойлуулав. Үүний дараа цайны технологийн горимыг тогтоож, цай үйлдвэрлэлийн схемээр ариутган савлаж, цайны хайрцаг, сав баглаа боодлын дизайныг гарган, үйлдвэрлэлд нэвтрүүлэх бүтээгдэхүүний загварыг гарган авлаа. Бүтээгдэхүүний бар кодыг баталгаажуулан, барааны тэмдэгт болон оюуны өмчийн патентийг мэдүүлээд байна.Түлхүүр үгс: нийлбэр флавоноид, нийт фенолт нэгдэл, антиоксидант идэвх, MNS стандарт